The Ethos of Religious Harmony of Javanese Muslims According to King Mangkunegara IV - ., Daryono; Anshori, Afif; Setiawati, Rini; Pimay, Awaludin; Syukur, Suparman; Dwianto, Agus (Journal of Ecohumanism, 2024)
In the framework of colonial discourse, this research investigates the Javanese Muslim ethos of religious concord as expressed in the writings of Mangkunegara IV. The study examines how Mangkunegara IV's beliefs embody a rejuvenation of traditional moral values, with the goal of addressing societal changes that occurred during Dutch colonial governance. The theoretical framework emphasizes three manifestations of kindness: universal respect and care, harmonious interpersonal relationships, and devotion to cultural or religious practices. The practical and reasonable demands of the sociocultural, political, and economic aspects of colonial life are reflected in these ideals. Strategies for implementation center on the goal of happiness and prosperity for everyone, tolerance, and humility; these values are consistent with modern pluralism, sustainable ethics, and compassionate progressivism. These tactics are examined using content analysis & hermeneutic approaches, taking meta-ethics and normative ethics into account. The research indicates that the ethical perspective of Mangkunegara IV provides significant perspectives for managing social disputes and fostering unity in Indonesia. In the framework of colonial discourse, this research investigates the Javanese Muslim ethos of religious concord as expressed in the writings of Mangkunegara IV. The study examines how Mangkunegara IV's beliefs embody a rejuvenation of traditional moral values, with the goal of addressing societal changes that occurred during Dutch colonial governance. The theoretical framework emphasizes three manifestations of kindness: universal respect and care, harmonious interpersonal relationships, and devotion to cultural or religious practices. The practical and reasonable demands of the sociocultural, political, and economic aspects of colonial life are reflected in these ideals. Strategies for implementation center on the goal of happiness and prosperity for everyone, tolerance, and humility; these values are consistent with modern pluralism, sustainable ethics, and compassionate progressivism. These tactics are examined using content analysis & hermeneutic approaches, taking meta-ethics and normative ethics into account. The research indicates that the ethical perspective of Mangkunegara IV provides significant perspectives for managing social disputes and fostering unity in Indonesia.